Cloud-based service for visual monitoring of the patient's functional state dynamics using the electrical bioimpedance parameters (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2021)
Background/Aim. The results of the development of its own cloud service and a flexible web interface of the electrical bioimpedance measurement system are presented. The purpose of this article is to investigate and describe additional cloud service which is posible to use in the problems of diagnosing body composition and its biohydration. The system provides the organization and convenient operational control of the diagnostic or therapeutic procedure based on the direct determination and dynamics of the constituent parameters of the electrical bioimpedance (module, phase angle, active and reactive components) in an extended frequency band.System implementation. The features and conditions for the implementation of such a system are considered on the example of the problem of diagnosing the dynamics of the water status of a person directly during an ultrafiltration session of the hemodialysis procedure. In this case, the structure combines an ``artificial kidney'' apparatus, a bioimpedance meter and a cloud service with processing and display of input data into a single system.Accumulation and analysis of clinical data. Measurement of electrical bioimpedance parameters is carried out at three fixed frequencies of 20 kHz, 100 kHz and 500 kHz in automatic mode during the entire ultrafiltration session. The data obtained through API during measurements is displayed in the web interface. Discussion and Conclusion. The indicated impedance parameters are used as diagnostic indicators, as well as the position of the impedance vectors on the complex plane relative to the ``tolerance ellipses''. Focusing on the dynamic changes in bioimpedance parameters, it is possible to objectively assess the functional state dynamic of the patient and correctness of any treatment procedure.